The Burden of Early Phenotypes and the Impact of Left Ventricular Wall Thickness on Hypertrophic Cardiomyopathy Sarcomere Mutation Carriers: Findings from the HCMNet Study - Ho, Carolyn Y. (JAMA Cardiol, 2017)
IMPORTANCE: Sarcomere mutations and left ventricular hypertrophy (LVH) are cardinal features of hypertrophic cardiomyopathy (HCM). However, little is known about the full spectrum of phenotypic manifestations, or how LVH impacts disease expression. OBJECTIVE: Genotyped individuals with or at risk for HCM were studied to: (1) characterize sarcomere mutation carriers (G+), including assessing collective phenotypic burden; and (2) investigate the relationship between left ventricular wall thickness (LVWT) and other disease features. DESIGN: Cross-sectional multicenter observational study SETTING: Network of hypertrophic cardiomyopathy specialty clinical centers (HCMNet). PARTICIPANTS: Mutation carriers with LVH (G+/LVH+), without LVH (G+/LVH-), and healthy related controls (G-/LVH-) were enrolled through HCMNet sites. A total of 193 participants were enrolled and underwent study procedures. Analyses were performed on 178 participants (G+/LVH+ n=81, G+/LVH- n=55, G-/LVH- n=42) with mean age 26.9, 20.4 and 17.5 years, respectively. EXPOSURE: The primary stratifying variables were the presence of a sarcomere mutation and measures of LV wall thickness. MAIN OUTCOMES AND MEASURES: Parameters from standardized exercise testing, echocardiography, cardiac magnetic resonance, serum biomarker measurement, and electrocardiography (ECG) were compared across study cohorts. RESULTS: G+/LVH- subjects had smaller LV cavity size and higher LV wall thickness (LVWT):diastolic diameter ratio and LV ejection fraction than controls. Phenotypic burden was determined as the cumulative number of 7 traits (ECG changes; decreased LV systolic, diastolic diameter, or septal E′; higher LVWT:diameter ratio; serum troponin, natriuretic peptide levels) in each individual. Mean burden was 4.9 in G+/LVH+, 2.4 in G+/LVH-, and 1.3 in controls (p<0.001). Classification and regression tree analysis identified an LVEDD z-score < -1.85 or the combination of LVEDD z-score ≥ -1.85 and Septal E′ z-score < -0.52 as having 74% accuracy in discriminating G+/LVH- subjects from controls. In mutation carriers, these traits and other parameters demonstrated a continuous relationship with LVWT; generally without clear cutoff signifying pathologic transition. CONCLUSIONS AND RELEVANCE: G+/LVH- individuals demonstrate altered cardiac dimensions and function and higher burden of early phenotypes. Two methods discriminated phenotypic subgroups – a sum across seven criteria and a tree-based rule that identifies constellations of distinguishing factors. Greater LVWT is associated with more prominent cardiac abnormalities in a continuous, although not always linear manner. A single value of LVWT could not dichotomize the presence or absence of disease.